Carbon nanohorn-derived graphene nanotubes as a platinum-free fuel cell cathode - Unni, SreeKuttan M.; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Puthenpediakkal, Hasna; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
Current low-temperature fuel cell research mainly focuses on the development of efficient nonprecious electrocatalysts for the reduction of dioxygen molecule due to the reasons like exorbitant cost and scarcity of the current state-of-the-art Pt-based catalysts. As a potential alternative to such costly electrocatalysts, we report here the preparation of an efficient graphene nanotube based oxygen reduction electrocatalyst which has been derived from single walled nanohorns, comprising a thin layer of graphene nanotubes and encapsulated iron oxide nanopartides (FeGNT). FeGNT shows a surface area of 750 m(2)/g, which is the highest ever reported among the metal encapsulated nanotubes. Moreover, the graphene protected iron oxide nanoparticles assist the system to attain efficient distribution of Fe-N-x and quaternary nitrogen based active reaction centers, which provides better activity and stability toward the oxygen reduction reaction (ORR) in acidic as well as alkaline conditions. Single cell performance of a proton exchange membrane fuel cell by using FeGNT as the cathode catalyst delivered a maximum power density of 200 mW cm(-2) with Nafion as the proton exchange membrane at 60 degrees C. The facile synthesis strategy with iron oxide encapsulated graphitic carbon morphology opens up a new horizon of hope toward developing Pt-free fuel cells and metal-air batteries along with its applicability in other energy conversion and storage devices.
Keywords: carbon nanohorns; carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction

Conjugated porous polymers as precursors for electrocatalysts and storage electrode materials - Bhosale, Manik E.; Illathvalappil, Rajith; Kurungot, Sreekumar; Krishnamoorthy, Kothandam (Chemical Communications, 2016)
Conjugated porous polymers were used as precursors to prepare nitrogen and sulphur doped carbon atoms, which were then used for oxygen reduction and energy storage.

Chitosan intercalated metal organic gel as a green precursor of fe entrenched and fe distributed N-doped mesoporous graphitic carbon for oxygen reduction reaction - Shijina, Kottarathil; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Yamaguchi, Takeo; Anilkumar, Gopinathan M.; Hareesh, U. S.; Sailaja, G. S. (Chemistryselect, 2017)
Herein, we present Metal-Organic Gel intercalated with chitosan, a `green'' precursor for the synthesis of intrinsic N-doped Fe entrenched (CHI-TMA-Fe-CW) and Fe distributed mesoporous graphitic carbon structures (CHI-TMA-Fe-CW-M1) with appreciable Oxygen Reduction Reaction (ORR) activity in alkaline medium. Modulation of the synthetic protocol as a function of reaction kinetics and gelation time while maintaining identical pyrolysis conditions (900 degrees C, flowing N-2 atmosphere) improves the microstructure, surface area and Fe distribution of the graphitic structures (CHI-TMA-Fe-CW-M1). CHI-TMA-Fe-CW has a Fe entrenched graphitic nanocapsule like morphology while Fe distributed mesoporous graphitic carbon sheets, with a specific surface area value of 565 m(2) g(-1) obtained by modulating the synthesis chemistry in CHI-TMA-Fe-CW-M1. The higher percentage of graphitic N in CHI-TMA-Fe-CW-M1 apparent from the XPS data validate that the modified synthetic method favours creation of more graphitic N sites contributing for better catalytic performance. CHI-TMA-Fe-CW-M1 catalyst exhibited comparable electrocatalytic activity with that of the commercially available Pt/C via an efficient four-electron-dominant ORR pathway with a positive onset potential value of 0.925 V vs RHE. Good durability of CHI-TMA-Fe-CW-M1 after 5000 cycles further confirm the prospects of MOG-chitosan and the feasibility to be used as a potential catalyst for ORR.
Keywords: electrocatalyst; fuel cell; Metal-Organic-Gel; oxygen reduction reaction

Carbon derived from soft pyrolysis of a covalent organic framework as a support for small-sized RuO2 showing exceptionally low overpotential for oxygen evolution reaction - Chakraborty, Debanjan; Nandi, Shyamapada; Illathvalappil, Rajith; Mullangi, Dinesh; Maity, Rahul; Singh, Santosh K.; Haldar, Sattwick; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (ACS Omega, 2019)
Electrochemical water splitting is the most energy-efficient technique for producing hydrogen and oxygen, the two valuable gases. However, it is limited by the slow kinetics of the anodic oxygen evolution reaction (OER), which can be improved using catalysts. Covalent organic framework (COF)-derived porous carbon can serve as an excellent catalyst support. Here, we report high electrocatalytic activity of two composites, formed by supporting RuO2 on carbon derived from two COFs with closely related structures. These composites catalyze oxygen evolution from alkaline media with overpotentials as low as 210 and 217 mV at 10 mA/cm(2), respectively. The Tafel slopes of these catalysts (65 and 67 mV/dec) indicate fast kinetics compared to commercial RuO2. The observed activity is the highest among all RuO2-based heterogeneous OER catalysts-a touted benchmark OER catalyst. The high catalytic activity arises from the extremely small-sized (similar to 3-4 nm) RuO2 nanoparticles homogeneously dispersed in a micro-mesoporous (BET = 517 m(2)/g) COF-derived carbon. The porous graphenic carbon favors mass transfer, while its N-rich framework anchors the catalytic nanoparticles, making it highly stable and recyclable. Crucially, the soft pyrolysis of the COF enables the formation of porous carbon and simultaneous growth of small RuO2 particles without aggregation.

A copper(ii)-coordination polymer based on a sulfonic-carboxylic ligand exhibits high water-facilitated proton conductivity - Tayade, Sakharam B.; Illathvalappil, Rajith; Lapalikar, Vaidehi; Markad, Datta; Kurungot, Sreekumar; Pujari, Bhatchandra; Kumbhar, Avinash S. (Dalton Transactions, 2019)
Proton conduction ability has been investigated in a new Cu(ii) based coordination polymer (CP), {[Cu-2(sba)(2)(bpg)(2)(H2O)(3)]center dot 5H(2)O}(n) (1), synthesized using the combination of 4-sulfobenzoic acid (4-Hsba) and bipyridine-glycoluril (BPG) ligands. Single crystal X-ray structure determination revealed that 1 features 1D porous channels encapsulating a continuous array of water molecules. Proton conductivity measurements reveal a high conductivity value of 0.94 x 10(-2) S cm(-1) at 80 degrees C and 95% RH. The activation energy (E-a) of 0.64 eV demonstrates that the solvate water, coordinated water and hydrophilic groups in the channels promote the mobility of protons in the framework. Water sorption measurements exhibited hysterical behaviour with a high uptake value of 379.07 cm(3) g(-1). Time-dependent measurements revealed that the proton conductivity is retained even after 12 h of measurements. The proton conduction mechanism was validated by ab initio electronic structure calculations using the Nudged Elastic Band (NEB) method with molecular dynamics (MD) simulation studies. The theoretical activation energy is calculated to be 0.54 eV which is in accordance with the experimental value.

Co (9) S (8) nanoparticle-supported nitrogen-doped carbon as a robust catalyst for oxygen reduction reaction in both acidic and alkaline conditions - Illathvalappil, Rajith; Kurungot, Sreekumar (ChemElectroChem, 2020)
The present work illustrates the synthesis of an efficient and durable catalyst for electrochemical oxygen reduction reaction (ORR) which is active both in the alkaline and acidic conditions by dispersing few-layer graphitic carbon coated Co(9)S(8)nanoparticles on the nitrogen-doped carbon (NVC-G) support (Co9S8/NVC-G). The size of the Co(9)S(8)nanoparticles is nearly 7-8 nm and the particles are found to be dispersed homogeneously on the NVC-G support. The few-layer graphitic carbon formed on the surface of Co(9)S(8)nanoparticles is assisting to accomplish their small size and it also prevents agglomeration of the nanoparticles. The ORR activity of the obtained material was analyzed in both 0.1 M KOH and 0.5 M H(2)SO(4)solutions. Co9S8/NVC-G displays nearly 70 mV overpotential compared to thestate-of-the-artPt/C in 0.1 M KOH solution. The half-wave potential (E-1/2) difference of the present system is nearly 75 mV with the commercial Pt/C. Co9S8/NVC-G displays promising ORR activity in the acidic conditions as well with nearly 140 mV overpotential compared to its Pt/C counterpart. The system shows about 170 mV lowerE(1/2)value with Pt/C. The system shows good stability both in acidic and basic conditions compared to the Pt/C system. Finally, testing of a single cell of a polymer electrolyte membrane fuel cell (PEMFC) was performed by employing Co9S8/NVC-G as the cathode catalyst and Nafion-212 as the proton exchange membrane. The system displays a maximum power density of 245 mW cm(-2)in H-2-O(2)and 115 mW cm(-2)in H-2-air feeding conditions.
Keywords: cobalt sulfide; fuel cells; Nanoparticles; nitrogen-doped carbon; oxygen reduction reaction

Cobalt-manganese modified theophrastite phase of nickel hydroxide nanoflower arrays on nickel foam as a self-standing bifunctional electrode for overall water electrolysis - Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Barik, Sidharth; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2023)
Designing and developing self-supported electrodes for water electrolysis is attractive as compared to conventional catalyst-coated electrodes. Herein, a (Co0.3Mn0.1Ni0.6)(OH)(2)/NF nanocomposite is prepared by anchoring (Co0.3Mn0.1Ni0.6)(OH)(2)via simple one-pot hydrothermal synthesis on nickel foam. The presence of Mn induces the external electronic structure of Co(OH)(2), and this also improves the electrochemically active surface area (ECSA). These favor better accessibility of active sites and increased intrinsic activity for the OER and HER. (Co0.3Mn0.1Ni0.6)(OH)(2)/NF has shown promising electrochemical activity toward the OER and HER in a 1 M KOH electrolyte, with an overpotential of 270 mV for the OER and 163 mV for the HER to deliver 10 mA cm(-2) current density. The overall water splitting was performed by employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as both the cathode and anode by displaying a voltage of 1.62 V at 10 mA cm(-2), which is comparable to that extracted from a similar system based on the state-of-the-art Pt/C@NF cathode and RuO2@NF anode (1.60 V at 10 mA cm(-2)) standard electrode pair. Interestingly, at high current densities, the (Co0.3Mn0.1Ni0.6)(OH)(2)/NF//(Co0.3Mn0.1Ni0.6)(OH)(2)/NF system displayed better overall water splitting performance (1.78 V at 100 mA cm(-2)) compared to its Pt/C@NF//RuO2@NF (1.89 V at 100 mA cm(-2)) counterpart while displaying a stable output during the evolution period that lasted for 24 h. The amounts of H-2 and O-2 produced are estimated to be 701.2 and 358.6 mmol, respectively, at a time interval of 1 h; these amounts correspond to an similar to 1 : 2 ratio of O-2 and H-2, respectively. This study confirms the capability for employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as a bi-functional and self-standing electrode for the realistic demonstrations of overall water splitting applications.